Survival and renal outcomes of direct heart transplant from veno-arterial extracorporeal membrane oxygenation support. (3rd October 2022) - Kanwal, A; Ohira, S; Levine, A; Isath, A; Pan, S; Dhand, A; Aggarwal-Gupta, C; Lanier, G M; Gass, A; Spielvogel, D; Kai, M
Abstract: Backgrounds: Patients on veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support are given the highest priority for cardiac transplantation (OHT) in the new UNOS heart allocation policy adopted in October 2018. Although patients may receive an organ quicker there may not be enough time to recover end-organ function. To date, little is known about survival and renal outcomes of direct OHT in patients that have been supported with VA-ECMO as a bridge to transplant due to limited experience in most transplant centers. Purpose: The aim of this study was to investigate survival and renal outcomes of direct OHT in patients supported with VA-ECMO prior to transplant. Methods: From January 2010 to February 2022, 23 patients who received single organ OHT alone directly from VA-ECMO support were retrospectively analyzed (16 patients after the new allocation policy). Kaplan-Meier analysis was used to estimate event-free survival. Results: The median age of recipients was 48 years. The median length of pre-transplant VA-ECMO support was 5 days. Additional pre-transplant support with intra-aortic balloon pump or Impella was utilized in 15 patients (65.2%) and 2 patients (9%) respectively. There was a trend toward improvement of serum creatinine after initiation of VA-ECMO support (Pre-ECMO: 1.66±1.22 mg/dl vs. Pre-OHT: 1.20±0.74 mg/dl, P=0.084). Four patients required preoperative renal replacement therapy (RRT); three were on RRT at the time of OHT. The median ischemic time of donor hearts was 168 minutes. VA-ECMO support was continued in 10 patients (43.5%) after OHT. Hospital mortality was 8.7% (2 patients). Post-transplant RRT was required in 9 patients (39.1%), and, of these, 5 patients were transitioned to permanent dialysis. Among the 14 patients who did not require post-transplant RRT, none required RRT during the follow-up period (median, 21.5 months). Kaplan-Meier survival analysis showed that estimated survival at 1 year and 3 years were 86.1%, and 77.5%, respectively (Figure 1A). The freedom from dialysis rate was 82.4% at 1 year, and 74.9% at 3 years (Figure 2A). Both survival (100% vs. 66.7%, P=0.008, Fig.1B) and dialysis free rate (100% vs. 55.6%, P=0.002, Figure 2B) at one-year were significantly worse in patients who required postoperative RRT. Conclusions: To our knowledge this is the largest single center study of OHT in patients that were supported with VA-ECMO. VA-ECMO as a bridge to end-organ recovery and OHT resulted in excellent outcomes. Patients who required post-transplant RRT more likely to require long-term dialysis, while those that did not receive RRT showed favorable outcomes. Overall survival in this patient population is comparable to patients that were not on VA-ECMO prior to transplant. Funding Acknowledgement: Type of funding sources: None.